¬Peirce’s Creative Hallucinations in the Ontogeny of Abductive Reasoning - West, Donna E (Public Journal of Semiotics, 2017)
This inquiry proposes that Peirce’s ultimate concept of dreams, which can be sub-divided in seven different functions, supply the raw material for habit-change inherent in every plausible inference. With references to developmental literature, I propose that dreams represent an outlet whereby children rely upon vivid directional icons of events (virtual habits) in reconciling logical anomalies provoked by unexpected happenings. Accordingly, dreams supply insights into how potential happenings materialize – identifying which factors can enhance/enrich the effectiveness of potential event outcomes. Dreams of this creative kind are not obsessional or socially driven but rather form the bedrock for conceiving of many meritorious insights, as shown in phenomena like children’s prelinguistic habits, word substitutions, overextensions, role-play and perspective taking.